PERAN MITRA STRATEGIS INDONESIA DALAM MENJAGA KEAMANAN MARITIM LAUT CINA SELATAN: Jonathan Jacob Paul Latupeirissa, Ni Ketut Arniti, Ni Luh Yuni Lestari - Jonathan Jacob Paul Latupeirissa (LPPM STIA Nusantara Sakti, 2023)
The World Maritime Axis Policy for Indonesia is important with a focus on the Indo-Pacific region with maritime cooperation that can continue to be strengthened with other countries in the region, both through ASEAN as a strategic regional organization and cooperation with countries outside ASEAN membership, including India. This research will use qualitative methods. The data in this study will be interpreted and then analyzed using a conceptual framework for securitization. Strategic partnerships provide freedom for Indonesia without being bound by alliance obligations, in which middle-power partners who are regionally relevant and have the same interests can collectively enhance Indonesia's defense capabilities. Deeper strategic partnerships with Japan, India and Australia can then be prospects that deserve further exploration because apart from this, it is a form of arrangement between middle powers countries that have shared values such as democracy, recognizing the importance of maritime security, preventing domination one hegemon in Asia, maintaining the free and open Indo-Pacific (including the security and stability of the South China Sea), respecting the sovereignty of each country, and surviving the vortex of great powers competition, cooperation between partner countries is also under policy principles Free Active and able to meet Indonesia's security needs.